Desensitization of delayed-type hypersensitivity in mice: suppressive environment - Takashi Katsura; Kazuo Kobayashi; Michio Hosaka; Sachiko Sugihara; Tsuyoshi Kasama; Keita Kasahara; Stanley Cohen; Takeshi Yoshida (Mediators of Inflammation)
The systemic injection of high doses of antigen into a preimmunized animal results in transient unresponsiveness of cell-mediated immune responses. This phenomenon is known as desensitization. Serum interleukin 2 (IL-2) activity was found transiently in desensitized mice at 3 h after the antigen challenge. These mice could not reveal antigen nonspecific delayed-type hypersensitivity (DTH) 1 d after the challenge. Specific suppression of DTH was observed at later stages. Sera from 3 h desensitized mice showed suppressive effects on DTH in preo immunized mice. Administration of recombinant IL-2 into preimmunized mice led to the failure of development of DTH to antigens. These observations suggest that IL-2 plays an important role in the suppressive environment.